FREEDOM OF CREATIVITY AND CREATIVE IMAGINATION. MAN AND HIS TIME - A. E. Razumov (Высшее образование в России)
Man as a creative personality desires for freedom as well as cognition and creative work as his essence. It should be noted, however, that what we know about ourselves and how we see ourselves are far from being the same thing. We live to a large extent in imaginary worlds, and they appear to us more actual than their real-life prototypes. Religion, art and science try to tackle this problem, and in each case an attention is being focused, respectively, on a different aspect of being. What is the most attractive for mind here is Mystery underlying this phenomenon. Imagination is inherent in every creative act, and in any such act do Time and History attend. Time effects on the outcomes of our efforts today. This, in the author’s view, is obviously demonstrated by the history of Russia, where its numerous present-day achievements and failures are determined by its past.